Job mobility in Turkey - Yusuf Emre Akgunduz; Altan Aldan; Yusuf Kenan Bagir; Huzeyfe Torun (Central Bank Review (CBR), 2019)
The degree and quality of job mobility is an important factor of optimal allocation of resources and growth in an economy. Job mobility facilitates productive employer-employee matches. In that respect, job mobility allows employees to work in industries which suit their skills and enables earning gains. It also supports industry level productivity gains by providing shift of employment from less productive firms to more productive ones. In this study, a descriptive analysis of job mobility is conducted using Entrepreneurship Information System data. The results suggest that job mobility is higher among young and men. In addition, more than half of the job movers switch to jobs in bigger, more productive and more profitable firms. Job mobility is intensive within manufacturing and trade-transportation industries and employees in mining, construction, public administration, education and health industries are more likely to switch to jobs in other industries. Finally, the determinants of job mobility between regions are analyzed and a positive relation between internal migration and intra-regional job mobility is found.
Keywords: 330; Job mobility; Employer-employee match; Labor reallocation